The marzipan pig - Hoban, Russell (New York Review children's collection., 2016)
The marzipan pig eaten by a mouse starts a chain of events involving the feelings of the mouse, a grandfather clock, an owl, a bee, a flower, and another mouse who in her turn discovers another marzipan pig to eat.